Immunological and Safety Considerations When Selecting the Dose Formulation of a Purified Inactivated Zika Virus Vaccine (PIZV) - Camilo J. Acosta; Francesco Nordio; Eloi Kpamegan; Kelley J. Moss; Pradeep Kumar; Kazuhiro Hirata (Microorganisms, 2024)
We previously reported the first-in-human assessment of three doses (2, 5, and 10 µg) of purified inactivated Zika virus vaccine (PIZV or TAK-426) in the Phase 1 ZIK-101 study (NCT03343626). Here, we report dose selection based on extended safety and immunogenicity data (6 months post-vaccination) and discuss considerations (e.g., immunological, historic, flavivirus immunological cross-reactions) for selecting a Zika virus (ZIKV) vaccine dose formulation. TAK-426 dose selection was conducted at the first interim analysis, and was based on cumulative safety data from both flavivirus-naïve (up to ≥28 days post-dose PD2) and flavivirus-primed participants (up to ≥28 days PD1), and on immunogenicity data from flavivirus-naïve participants only (at 28 days PD1 and 28 days PD2). The safety profile from TAK-426 recipients was compared to placebo recipients. Immunogenicity was assessed by geometric mean titer ratios of neutralizing anti-ZIKV antibodies and differences in seroconversion rates. There was no significant difference in safety between the three TAK-426 doses. The 10 μg dose provided the earliest and strongest immune response (with close to 100% seroconversion and higher antibody titers PD1 in flavivirus-naïve participants), and was well tolerated with acceptable safety profiles in both flavivirus-naïve and flavivirus-primed participants; this dose was selected for further development.